Critical thinking implementation in an English education course: Why is it so challenging? - Agnes Riska Pravita; Paulus Kuswandono (EduLite: Journal of English Education, Literature and Culture, 2021)
Critical thinking has been acknowledged essential in education field but there have been debates on unclear instruction in implementing critical thinking skill in the classroom. Due to the urgency on the needs of critical thinking skill cultivation, this research aims to investigate the implementation of critical thinking skill instructional strategies in Critical Reading and Writing I and the students’ perception towards their critical thinking skill in CRW I. In order to attain the data, the researchers employed mixed-method. Observation sheet, interview guidelines, close-ended and open-ended questionnaires were utilized. The data of the close-ended questionnaire set in the Likert Scale distributed to 17 students was analyzed by measuring the central tendency or the mean and it indicates that the value of the students’ perceived critical thinking skills is 3.89 (middle to high) in which the highest 4.18 is on interpretation skill and the lowest 3.71 is analysis skill. Meanwhile, for the open-ended questionnaire, the data was analyzed utilizing coding procedure. Further, in analyzing the data of the interview, the researchers recorded the data into transcripts and analyzed them utilizing selective coding and it reveals that the instructional strategies used are explicit instruction, teacher questioning and active and cooperative learning.